Microglial immune regulation by epigenetic reprogramming through histone H3K27 acetylation in neuroinflammation - Huang, Minhong; Malovic, Emir; Ealy, Alyssa; Jin, Huajun; Anantharam, Vellareddy; Kanthasamy, Arthi; Kanthasamy, Anumantha G. (Frontiers in Immunology, 2023)
Epigenetic reprogramming is the ability of innate immune cells to form memories of environmental stimuli (priming), allowing for heightened responses to secondary stressors. Herein, we explored microglial epigenetic marks using known inflammagen LPS as a memory priming trigger and Parkinsonian-linked environmental neurotoxic stressor manganese (Mn) as the secondary environmental trigger. To mimic physiological responses, the memory priming trigger LPS treatment was removed by triple-washing to allow the cells’ acute inflammatory response to reset back before applying the secondary insult. Our results show that after the secondary Mn insult, key proinflammatory markers iNOS level (nitrite release and mRNA expression/protein), Il-6, Il-α and cytokines were exaggerated in LPS-primed microglia. Our paradigm implies primed microglia retain immune memory that can be reprogrammed to augment inflammatory response by secondary environmental stress. To ascertain the molecular underpinning of this neuroimmune memory, we further hypothesize that epigenetic reprogramming contributes to the retention of a heightened immune response. Interestingly, Mn-exposed, LPS-primed microglia showed enhanced deposition of H3K27ac and H3K4me3 along with H3K4me1. We further confirmed the results using a PD mouse model (MitoPark) and postmortem human PD brains, thereby adding clinical relevance to our findings. Co-treatment with the p300/H3K27ac inhibitor GNE-049 reduced p300 expression and H3K27ac deposition, decreased iNOS, and increased ARG1 and IRF4 levels. Lastly, since mitochondrial stress is a driver of environmentally linked Parkinson’s disease (PD) progression, we examined the effects of GNE-049 on primary trigger-induced mitochondrial stress. GNE-049 reduced mitochondrial superoxide, reduced mitochondrial circularity and stress, and decreased mitochondrial membrane depolarization, suggesting beneficial consequences of GNE-049 on mitochondrial function. Collectively, our findings demonstrate that proinflammatory primary triggers can shape microglial memory via the epigenetic mark H3K27ac and that inhibiting H3K27ac deposition can prevent primary trigger immune memory formation and attenuate subsequent secondary inflammatory responses.